2010
DOI: 10.1016/j.watres.2010.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and molecular analyses for fecal indicator bacteria in non-point source subtropical recreational marine waters

Abstract: The use of enterococci as the primary fecal indicator bacteria (FIB) for the determination of recreational water safety has been questioned, particularly in sub/tropical marine waters without known point sources of sewage. Alternative FIB (such as the Bacteroidales group) and alternative measurement methods (such as rapid molecular testing) have been proposed to supplement or replace current marine water quality testing methods which require culturing enterococci. Moreover, environmental parameters have also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
123
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 51 publications
2
123
0
Order By: Relevance
“…Little was known about the relationship of enterococci and other FIB to human health in recreational waters contaminated by nonpoint sources when the regulations were promulgated (115). Recently, some studies found an association between densities of enterococci and illness rates at beaches impacted by nonpoint sources of contamination (104,304). While there was an increased incidence of gastrointestinal illness, respiratory illness, and skin illness in bathers in one study (104), the only health effect with a dose-response relationship to concentrations of indicator bacteria in both studies was skin illnesses (104,304).…”
Section: Use Of Enterococci As Fecal Indicator Bacteriamentioning
confidence: 98%
See 1 more Smart Citation
“…Little was known about the relationship of enterococci and other FIB to human health in recreational waters contaminated by nonpoint sources when the regulations were promulgated (115). Recently, some studies found an association between densities of enterococci and illness rates at beaches impacted by nonpoint sources of contamination (104,304). While there was an increased incidence of gastrointestinal illness, respiratory illness, and skin illness in bathers in one study (104), the only health effect with a dose-response relationship to concentrations of indicator bacteria in both studies was skin illnesses (104,304).…”
Section: Use Of Enterococci As Fecal Indicator Bacteriamentioning
confidence: 98%
“…Recently, some studies found an association between densities of enterococci and illness rates at beaches impacted by nonpoint sources of contamination (104,304). While there was an increased incidence of gastrointestinal illness, respiratory illness, and skin illness in bathers in one study (104), the only health effect with a dose-response relationship to concentrations of indicator bacteria in both studies was skin illnesses (104,304). Furthermore, in a comparison of analytical methods, the dose-response relationship for skin illness was seen only with samples analyzed by membrane filtration (304).…”
Section: Use Of Enterococci As Fecal Indicator Bacteriamentioning
confidence: 99%
“…Numerous studies have shown that beach sand may serve as a reservoir for pathogens harmful to human health and indicator microbes that can be released into surrounding waters through tidal action or run-off (Alm et al, 2003;Whitman and Nevers, 2003;Boehm and Weisberg, 2005;Beversdorf et al, 2007;Colford et al, 2007;Fleisher et al, 2010;Ge et al, 2010;Sinigalliano et al, 2010;Abdelzaher et al, 2010). Several authors have reported that both indicator bacteria and potential pathogens occur in beach sands of both freshwater and marine environments (Sanchez et al, 1986;Ghinsberg et al, 1994Ghinsberg et al, , 1995Obiri-Danso and Jones, 2000;Desmarais et al, 2002;Sato et al, 2005;Vantarakis et al, 2005;Beversdorf et al, 2007;Bonilla et al, 2007;Vogel et al, 2007;Hartz et al, 2008;Abdelzaher et al, 2010).…”
Section: Bacteriamentioning
confidence: 99%
“…Due to this risk to human health, it is important to assess the contribution of microorganisms harbored in beach sediment to the overall quality of the beach and associated recreational water (Phillips et al, 2011b). High enterococci levels in beach water represent an increased health risk for beachgoers who enter the water Sinigalliano et al, 2010). In fact, a pilot epidemiological study conducted by Bonilla et al (2007) demonstrated that gastrointestinal illness in beach users was associated with exposure to water and intertidal sand, whereas contact with the sand in upper beach areas did not result in such illnesses (Pinto et al, 2012).…”
Section: Bacteriamentioning
confidence: 99%
“…S. aureus is commonly detected at recreational beaches in both seawater and sand (32)(33)(34)(35)(36), suggesting that the recreational water environment may be an important reservoir for S. aureus. Epidemiology studies have found associations between recreational water contact and skin ailments (37)(38)(39)(40), further pointing to recreational water exposure as a transmission route for pathogenic S. aureus.…”
mentioning
confidence: 99%